Surface Modification of Materials by Atmospheric-Pressure Plasma to Improve Impregnation with Essential Oils for the Control of Tropilaelaps Mites in Honeybees (Apis mellifera) - Thummanoon Boonmee; Laedlugkana Wongthaveethong; Chainarong Sinpoo; Terd Disayathanoowat; Jeffery S. Pettis; Veeranan Chaimanee (Applied Sciences, 2022)
In this research, the absorption and release rate of the essential oil, Amomum krervanh, by seven different materials were evaluated. Cardboard showed the highest EO absorption capacity (0.93 ± 0.0052 μL of oil/mg of dry cardboard) followed by balsa wood and drawing board with the EO absorption of 0.77 ± 0.043 and 0.62 ± 0.010 μL of oil/mg of dry material, respectively. The results also demonstrated that cardboard had the highest EO retention (52.84 ± 0.687% after 20 min of analysis). Additionally, the essential oil was released from the drawing board and cardboard at the same rate during the observation period. Surface modification of drawing board and cardboard was performed using atmospheric-pressure plasma for enhancing the material properties for Tropilaelaps control. The absorption capacity of cardboard was decreased after plasma treatment at an argon flow rate of 0.25 and 0.5 Lpm for 60 s/cm2. However, the atmospheric-pressure plasma did not change the EO release property of these materials. Scanning electron microscopy analyses indicated a fractured and scaly surface after plasma treatment of gas flow rate at 0.5 Lpm and 1.0 Lpm for 30 s/cm2. The surface chemical composition of materials was not altered following plasma treatment. Although the number of mite-infested brood cells did not differ significantly between treatment groups at the end of the field experiment, Tropilaelaps spp. populations in the plasma-treated cardboard impregnated with EO 5% (v/v) treatment were lower on days 7–14 of the experiment. Thus, parameters related to the atmospheric-pressure plasma should be further optimized to improve the material surfaces for use with essential oils to control honeybee mites.